Plant biochemistry - Heldt, Hans-Walter; Piechulla, Birgit (Academic Press is an imprint of Elsevier, 2021)
Plant Biochemistry, Fifth Edition, enables students to gain basic knowledge of the entire field, from photosynthesis to genetic engineering and its many commercial applications. Topics include cell structure and function of isoprenoids, phenylpropanoids and other secondary metabolites, and plant growth regulation and development. The text covers recent research findings and identifies areas of future research. This book is suitable for graduate students and advanced undergraduates in plant physiology, plant pathology, plant cell biology, and other plant sciences, researchers in industries actively involved in agribusiness, other biotechnology enterprises, and researchers in agronomy, agriculture, plant development and related areas.